2017
DOI: 10.1093/carcin/bgw208
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Rev1 promotes the development of carcinogen-induced intestinal adenomas via accumulation of point mutation and suppression of apoptosis proportionally to the Rev1 expression level

Abstract: SummaryThis study describes the generation of a novel transgenic Rev1-overexpressing transgenic mouse and the role of Rev1 expression level on chemically induced tumorigenesis. Following MNU treatment, Rev1 promoted mutagenesis and suppressed apoptosis in proportion to the level of overexpression, resulting in accelerated tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Additionally, these differences in mutation signature may be due to low (or no) Rev1 translesion 5 DNA synthesis in colon tissue, which is the only DNA polymerase known to insert cytosine nucleobases opposite abasic sites (Lawrence, 2002). In support, Rev1 overexpression was necessary to stimulate polyp formation and enhance mutagenesis in an MNU-dependent murine intestinal adenoma model (Sasatani et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, these differences in mutation signature may be due to low (or no) Rev1 translesion 5 DNA synthesis in colon tissue, which is the only DNA polymerase known to insert cytosine nucleobases opposite abasic sites (Lawrence, 2002). In support, Rev1 overexpression was necessary to stimulate polyp formation and enhance mutagenesis in an MNU-dependent murine intestinal adenoma model (Sasatani et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…Here we have introduced several mouse models with disruptions in Rev1 functions, including the Rev1 Tg mouse model generated in our laboratory. Recently we have reported that in Rev1 Tg mice the elevated Rev1 expression allows cells with mutations to survive after DNA damages, resulting in an acceleration of tumorigenesis [47,48]. However, in vivo data like this is almost completely absent from the literature.…”
Section: Discussionmentioning
confidence: 98%
“…No significant effect on overall survival or tumor incidence was observed, suggesting that overexpression of Rev1 by itself is not sufficient to stimulate tumorigenesis. However, our study revealed that overexpression of Rev1 promotes development of chemically-induced tumors, namely azoxymethane (AOM)-induced hepatocellular carcinoma, and N-methyl-N-nitrosourea (MNU)-induced thymic lymphoma and intestinal adenomas (Sasatani et al, manuscript in preparation) [47,48]. Furthermore, in a comparative analysis of MNU-induced carcinogenesis in Rev1 Tg (Homo) mice, which are homozygous (Tg+/Tg+) for the Rev1 transgene, versus heterozygous Rev1 Tg mice, we provided evidence that Rev1 overexpression accelerates tumorigenesis in proportion to the Rev1 expression level.…”
Section: Rev1 Tg Micementioning
confidence: 93%
See 2 more Smart Citations